A Morbid Affair: Epidemics and Famine in Morocco, 1860–1888 - Madia THOMSON (Ученые записки Института Африки Российской академии наук)
Drought and famine have been long been important events in Moroccan history and the second-half of the nineteenth century was no different. A series of such crises occurred from the 1860’s to the 1880’s, at a time when Morocco was already feeling the pressure of European expansion and the subsequent strain on its traditional trade networks. The disruption of trade networks as well as local food shortages resulting from these climatic disturbances often pushed people to migrate to major cities in search of relief. Often unable to migrate as families, individuals might leave their children in the care of others with the hope of collecting them after the crisis. An unfortunate choice but one that might just allow someone to survive. Environmental crises resulting in famine have long been a cause of global concern. In his seminal work Poverty and Famines: an essay on entitlement, Amartya Sen explains the critical role of entitlement in mitigating the effects of famine on a given population (1981). For the purposes of this article, we will focus primarily on his concept of ‘own labour’ and “production- based” entitlement. In its discussion of nineteenth-century Morocco, the article lends an historical perspective to the modern system of national and international cooperation during environmental crises. That one no longer hears of people dying from such crises in Morocco suggests that death and famine are not necessary consequences of environmental disaster but rather the result of a lack of ideas and infrastructure.